Етапи просування інтернет-магазину в соціальній мережі Instagram - Сальо, Марія; Марковець, Олександр (Видавництво Львівської політехніки, 2019)
The thesis explores how social networking helps business development. It is determined that the main advantages of purchases in social networks is saving of time, lower price, studying exact characteristics of goods or services, review of a large number of photographs or video live. It is also explored that Instagram is one of the most promising social networks for business promotion, its benefits and capabilities.
Keywords: соціальні мережі; просування; інтернет-магазин; популярність; Instagram; Інтернет